Закономірності і парадокси в алелопатії вищих рослин: ретроспективний погляд - Golovko, E.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
Historical and analytical review of formation and development fundamental allelopathy in Ukraine have been given. Theoretical and experimental studies by academician A.M. Grodzinsky and his coworkers have been generalized. The most priority elaborations in modern allelopathy from description of ecological mechanisms between higher plants and microorganisms to isolation and identification of physiologically active substances have been considered.